From single particle impact behaviour to modelling of impact mills - Vogel, Lutz; Peukert, Wolfgang (Chemical Engineering Science, 2005)
An approach to quantify the impact grinding performance of different materials is presented. Based on a dimensional analysis and on fracture mechanical considerations two material parameters, fMat. and Wm,min, are derived from theoretical considerations. fMat. characterises the resistance of particulate material against fracture in impact comminution. Wm,min gives the mass specific energy which a particle can absorb without fracture. Using this approach various materials in a wide size range, e.g. different polymers, crystalline substances, glass and limestone, can be characterised quantitatively. The derived material parameters are applied to the systematic and multi-scale modelling of grinding in impact mills. A population balance model is presented and the results of the simulation for two different impact mills are shown. The developed model allows for a clear separation of the influence of material properties, mill specific features and operating conditions, thus enabling a deeper understanding of the impact grinding process. © 2005 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.tech.ITC.mechve.fromsi
Keywords: Comminution; Grinding; Impact mills; Material characterisation; Population balance model; Simulation